MODERNIZATION OF THE SYSTEM OF PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION AND SPORTS SPECIALISTS BASED ON INNOVATIVE TECHNOLOGIES (Academia Science Repository, 2023)
In this article, the combination of all professional skills in professional activity is the teacher's professional skills, the conditions for training future specialists in the field of physical education and sports, pedagogical competence is a wide range of pedagogical, psychological, social, medical and other issues are analyzed. The direction of development of education in the field of "Physical Education" has shown that until now students have mastered the skills and competencies of "Sports" in the field, and this is the main final goal of the effectiveness of physical education and was practically the only criterion. Students should fill them according to their individual characteristics to solve motor problems in various non-standard situations, with a creative perception of movements. the article offers such problems and their solutions